Dwarfs in disguise: multiple spinal abscesses and spondylodiscitis caused by an Enterococcus faecium small-colony variant. Issue 1 (27th March 2019) - Höring, Steffen; Sobotta, Katharina; Schneider, Sylke; Löffler, Bettina; Rödel, Jürgen
Abstract : Small-colony variants are slow-growing subpopulations of bacteria known to be involved in latent or recurrent infections, especially in deep-seated foci. Their atypical growth in small colonies can hamper prompt and correct identification in clinical specimens. Here, we present the first case of multiple spinal abscesses and spondylodiscitis associated with an Enterococcus faecium small-colony-variant in an immunocompetent patient. This case demonstrates the diagnostic challenges when encountering this phenotype in the diagnostic laboratory.